2018
DOI: 10.1111/jeu.12704
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence and Endemism of Trypanosomatids on a Small Caribbean Island

Abstract: We describe the monoxenous trypanosomatids parasitizing true bugs and flies on the island of Curac ßao. Out of 248 examined true bugs belonging to 17 species, 93 individuals were found to be infected (overall 38% prevalence) by at least one trypanosomatid species (referred to as typing units; TUs). Out of 80 flies, six were infected. All detected trypanosomatids were compared based on their 18S rRNA sequences with TUs parasitizing bugs and flies described from mainland South America, allowing us to assess thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
(100 reference statements)
1
9
0
Order By: Relevance
“…pyrrhocoris LBVs can be explained by a restricted host range of L . pyrrhocoris , which infects predominantly firebugs [ 4 , 26 ]. This resulted in the evolutionary preservation of the ancestral forms with the full-length M and S segments.…”
Section: Resultsmentioning
confidence: 99%
“…pyrrhocoris LBVs can be explained by a restricted host range of L . pyrrhocoris , which infects predominantly firebugs [ 4 , 26 ]. This resulted in the evolutionary preservation of the ancestral forms with the full-length M and S segments.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a study on the presence of trypanosomatids in Austrian mosquitoes revealed that 12 out of 19 species harbored these parasites with a prevalence ranging from 16% to 61% [ 8 ]. In other studies, trypanosomatids were identified in eight species of Drosophila analyzed in southwest Ohio (USA), with a prevalence of 1–17% [ 9 ], and the prevalence of trypanosomatids on insects in the island of Curaçao and Papua New Guinea was 38% and 15%, respectively [ 10 , 11 ]. In addition, the presence of monoxenous parasites has been identified in 4.3% of tsetse flies collected in the Dzanga-Sangha Protected Area (Central African Republic) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the last decade has seen a significant expansion of the known diversity of insect and plant trypanosomatids including some studies from Asia, Europe and Africa (Votýpka et al, 2010(Votýpka et al, , 2012aLukeš et al, 2018;Frolov et al, 2019Frolov et al, , 2020, it was continental South and Central America where most sampling occurred (Teixeira et al, 1997(Teixeira et al, , 2011Maslov et al, 2007Maslov et al, , 2010Borghesan et al, 2013;Kozminsky et al, 2015;Dario et al, 2021). However, except for a single study conducted on the island of Curacao (Votýpka et al, 2019), so far, no information was available on these interesting protists in the Caribbean. Here, we present such a study from Cuba, in which we have not only mapped the distribution and diversity of trypanosomatids but also applied ONT sequencing to examine their frequency and extent of co-infections within a single insect host.…”
Section: Discussionmentioning
confidence: 99%